1986
DOI: 10.1038/324476a0
|View full text |Cite
|
Sign up to set email alerts
|

Pancreastatin, a novel pancreatic peptide that inhibits insulin secretion

Abstract: In mammalian tissues the C-terminal amide structure has been found to occur only in neuroactive or hormonally-active peptides. About half known neuropeptide and peptide hormones have this unique chemical feature. Using a chemical detection method, a search for previously unknown peptides that possess the C-terminal amide structure in extracts of brain and intestine was carried out and a number of novel neuropeptides and hormonal peptides, designated neuropeptide Y, PHI, peptide YY, galanin and neuropeptide K w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
317
1
5

Year Published

1994
1994
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 672 publications
(327 citation statements)
references
References 15 publications
4
317
1
5
Order By: Relevance
“…Although their biological function is not yet well established, it has been suggested that they may play a central role in facilitating protein sorting to the regulated pathway as well as serving as precursors for biologically active peptides (i.e. the generation of pancreastatin by proteolytic cleavage of chromogranin A) [143,144]. In vitro, secretogranin II has been shown to aggregate and precipitate when the pH was lowered to 5.2 and the Ca21 concentration raised to lOmM [104].…”
Section: The Example Of the Secretograninsmentioning
confidence: 99%
“…Although their biological function is not yet well established, it has been suggested that they may play a central role in facilitating protein sorting to the regulated pathway as well as serving as precursors for biologically active peptides (i.e. the generation of pancreastatin by proteolytic cleavage of chromogranin A) [143,144]. In vitro, secretogranin II has been shown to aggregate and precipitate when the pH was lowered to 5.2 and the Ca21 concentration raised to lOmM [104].…”
Section: The Example Of the Secretograninsmentioning
confidence: 99%
“…Based on intracellular distribution studies [7,8] and on data obtained in other cell lines (AtT20 and PC12), these granins are believed to play important roles both in the sorting, packaging and processing of secretion products [11][12][13][14], and in the storage of Ca 2+ within SG lumina [15]. Moreover chromogranin A and/or peptides derived from its processing have been reported to play autocrine, paracrine and endocrine functions upon discharge [16][17][18][19], while CgB has been shown to induce an autocrine inhibition of insulin release from beta cells [20]. However, the functional significance of the latter process in the intact animal remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…3). These are (i) the vasostatin/fl-granin peptides, comprising the N-terminal 113 amino acids (flgranin/vasostatin II) of CGA and in some tissues (except in rat) a shorter N-terminal 76-amino acid polypeptide (vasostatin I) [91,103,104], (ii) pancreastatin [21,105], (iii) WE-14 [86,106,107] and (iv) the parastatin/GE-25 peptides [88,108,109]. Each of the peptides above have been demonstrated to exist in endocrine tissues by extraction, isolation, purification and peptide sequencing.…”
mentioning
confidence: 99%